Operational Efficiency of Suberkrub and Polyvalent Otterboards for Target specific In-shore Semi-pelagic Trawling - V., Vijayan; Dawson, Percy; M.D, Varghese; P., George Mathai; M.V., Baiju (Fishery Technology, 2025)
Otterboards, the stabilizing devices for trawl nets while under tow, function as hydrodynamically dependent means for holding the trawl mouth open. To be optimally effective, shearing power attained by them should be as high as possible and their resistance to motion should be as low as possible. As bent or moulded doors meet these requirements, 1407x982 mm Polyvalent and 1350x1000 mm high aspect ratio Suberkrub doors were rigged and experimented with 18.0 m RMT 8P semipelagic trawl having 80% side panels and 20.0 m double bridles to assess the functional efficiency of these combinations in inshore semipelagic trawling practices in the waters off Cochin, onboard 17.5m OAL stern trawler (277 hp). Design and operational details of these boards are described along with the catch composition obtained. The catch data analysed using ANOVA technique and done separately for quality fish and other catches, indicated no significant difference between these two designs of otterboards at 5% level, leading to a conclusion that both the designs experimented were equally efficient in combination with 18.0 m semipelagic trawl for the capture of inshore off-bottom resources